2022
DOI: 10.1029/2021wr030742
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Attribution of the Influence of Urban and Tree Cover Change on Streamflow: A Comparison of Large Sample Statistical Approaches

Abstract: Shifts in climate characteristics, such as precipitation totals, phase, and timing are widely considered to be the dominant drivers of hydrologic change, but land cover changes, consisting of changes in the biological or physical features present in a landscape (e.g., forested or urban area), also have the potential to drive changes in streamflow, potentially even offsetting the influence of climate (Slater, Anderson, et al., 2021). The effects of land cover changes on hydrological extremes, such as worsening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 84 publications
(146 reference statements)
3
19
0
Order By: Relevance
“…The greater contribution of urbanisation to low flow may also be due to the development of sewer systems and hard drainages associated with urbanisation, which potentially cause more sewage discharge and/or water imports and thus increase low flows. Our detected percentage change in flow quantiles is consistent with unit changes reported by Anderson et al (2022), who found a 0.6-0.7 % increase in mean and high flows for 1 % increase in urban area using panel regression for 729 US catchments. Some studies have reported a higher value, for example, Blum et al (2020) found a 3.3 % increase in annual maximum flood for a 1 % increase in impervious basin cover using 280 US catchments; Yang et al (2021) found a 3.9 % increase in annual maximum discharge for a 1 % increase in urban area using 757 catchments in China.…”
Section: Assessment Of the Contribution Of Urbanisation To Non-statio...supporting
confidence: 91%
See 3 more Smart Citations
“…The greater contribution of urbanisation to low flow may also be due to the development of sewer systems and hard drainages associated with urbanisation, which potentially cause more sewage discharge and/or water imports and thus increase low flows. Our detected percentage change in flow quantiles is consistent with unit changes reported by Anderson et al (2022), who found a 0.6-0.7 % increase in mean and high flows for 1 % increase in urban area using panel regression for 729 US catchments. Some studies have reported a higher value, for example, Blum et al (2020) found a 3.3 % increase in annual maximum flood for a 1 % increase in impervious basin cover using 280 US catchments; Yang et al (2021) found a 3.9 % increase in annual maximum discharge for a 1 % increase in urban area using 757 catchments in China.…”
Section: Assessment Of the Contribution Of Urbanisation To Non-statio...supporting
confidence: 91%
“…Some studies have reported a higher value, for example, Blum et al (2020) found a 3.3 % increase in annual maximum flood for a 1 % increase in impervious basin cover using 280 US catchments; Yang et al (2021) found a 3.9 % increase in annual maximum discharge for a 1 % increase in urban area using 757 catchments in China. The variations in the magnitude may be due to the different statistical approaches (Anderson et al, 2022;Salavati et al, 2016), as well as the sampling sizes and methods (Blum et al 2020).…”
Section: Assessment Of the Contribution Of Urbanisation To Non-statio...mentioning
confidence: 99%
See 2 more Smart Citations
“…Observations show that deforestation in 56 developing countries increased flood occurrence during the last decades (Bradshaw et al, 2007). Similarly, Anderson et al (2022) show that urbanization and re-forestation have respectively increased and decreased extreme streamflow, in the context of 729 US catchments. Similar indications emerge from many modeling studies (e.g., Du et al, 2012).…”
Section: Hydrological Change Has Occurredmentioning
confidence: 99%